Influência da lesão condral na concentração de glicosaminoglicanas sulfatadas no líquido sinovial - Cintra Neto, Paulo Felix de Araujo (2006)
Objective. To evaluate the influence of sulfated glycosaminoglycan (GAG) concentration in synovial fluid from individuals with chondral injuries, either isolated or associated with anterior cruciate ligament injury or meniscal injury, and check for an association between time since injury and the degree of chondral injury. Material and Method. Twenty-nine adult subjects (25 men and 4 women, mean age 38.3 ± 10.9 years) were selected. Samples obtained from all subjects were quantified to determine the GAG concentration using dimethylmethylene blue dye. The degree of chondral damage was macroscopically evaluated by arthroscopy and rated according to the International Cartilage Repair Society (ICRS) classification. Results. Significant differences were found concerning the GAG concentration in the control group compared with the other groups (p<0.05). No significant differences were found between the studied groups concerning time since injury and degree of chondral damage according to the ICRS. A strong correlation was found between GAG concentration and time since injury in the chondral injury group (r= -1). Conclusion. Damage to articular structures seems to be the determining factor in the change of synovial fluid GAG concentration, being higher in isolated chondral injury. When associated with anterior cruciate ligament rupture and/or meniscal injury, it will promote a tendency to fall, and is not related to sex, age, time since injury and degree of chondral injury in all groups studied.